2005
DOI: 10.2355/isijinternational.45.1272
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Simulation of Flow and Combustion for Pulverised Coal Injection

Abstract: A three-dimensional numerical model of pulverised coal injection has been developed for simulating coal flow and combustion in the tuyere and raceway of a blast furnace. The model has been used to simulate previously reported combustion tests, which feature an inclined co-axial lance with an annular cooling gas. The predicted coal burnout agrees well with that measured for three coals with volatile contents and particle size ranging between 20.2-36.4 % and particle sizes 1-200 mm. Many important phenomena incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…Figure 15 shows more comparisons with the measurements, at a specific position downstream (925 mm from lance tip) under a wide-range of O/C ratio (atomic O-to-C) from 1.85-3.97 ( Table 8). The results indicate that, the final burnouts at that position predicted using the present and previous models appear similar, and they are both comparable to the measured data 17,33) at 925 mma sampling point far away from the lance tip. That is, the two model are both correct for the burnout prediction at this point, in spite of omitted char gasification reactions in the previous models.…”
Section: Comparison With the Previous Modelsupporting
confidence: 85%
See 2 more Smart Citations
“…Figure 15 shows more comparisons with the measurements, at a specific position downstream (925 mm from lance tip) under a wide-range of O/C ratio (atomic O-to-C) from 1.85-3.97 ( Table 8). The results indicate that, the final burnouts at that position predicted using the present and previous models appear similar, and they are both comparable to the measured data 17,33) at 925 mma sampling point far away from the lance tip. That is, the two model are both correct for the burnout prediction at this point, in spite of omitted char gasification reactions in the previous models.…”
Section: Comparison With the Previous Modelsupporting
confidence: 85%
“…To date, a few 3D studies have been reported in the literature. [13][14][15][16][17] Murai et al 13) and Goto et al 14) reported a 3D simulation for blowpipe and on this basis some lance arrangements were examined for co-injections of coal/plastic and coal/gas. Du et al 15) reported a model for blowpipe and tuyere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, commercial software was utilized to simulate coal de-volatilization and combustion in a combustion chamber [22] and in a tuyere-raceway system with an assumed raceway shape [23] . The particle phase was treated as a dispersed phase using a Lagrangian method and a stochastic model was used to calculate particle turbulent dispersion.…”
Section: Existing Cfd Modelsmentioning
confidence: 99%
“…The heterogeneous char reaction rate is assumed to be of first-order with respect to oxygen, carbon dioxide and water vapor concentrations [22] .…”
Section: Char Combustion Ratementioning
confidence: 99%